PEMANFAATAN FUNGI Aspergillus flavus, Aspergillus terreus, DAN Trichoderma harzianum UNTUK MENINGKATKAN PERTUMBUHAN BIBIT Avicennia marina - Lestari Marbun; Yunasfi Yunasfi; Miswar Budi Mulya (Program studi Kehutanan USU, 2015)
The benefit of A. marina nursery is to provide A. marina mangrove seed that has good quality. Mangrove vegetation A. marina can survive in site conditions that have accumulated metals with the help of fungi that neutralize the accumulation of metals. Each of result has correlation which strong to A. marina growth. This research can provide information on the types of fungi who has capability to improve growth of A.marina. this research was conducted from September 2014 until May 2015 using a completely randomized design (CRD) with treatment application types of fungi and five replications. There are three type of fungi namely A. flavus, A.tereus, and T.harzianum. Application of Trichoderma harzianum gave the best result on seedling growth parameters A. marina, with a diameter of 0,392 cm, an average height of 1,3 g, and a leaf area of 28,08 cm. A. terreus gave the best result on seedling growth parameters A. marina with an average height 20,22 cm and a diameter of 0,392 cm.Keyword: fungi, Avicennia marina, mangrove, nursery.